Resíduos poliméricos: quantificação, caracterização, lavagem e tratamento do efluente gerado no processo - Streit, Angélica Fátima Mantelli (2016)
With the industrialization, the demographic growth and the consumption patterns of society there is an increase in the generation of solid waste, among which include polymeric waste. Thereby, the recycling emerges as a viable alternative, but for it to be effective is very important to carry out the cleaning of the waste, as well as the treatment of wastewater generated in the process. Thus, the main objective of this study was performed quantification, characterization and washing of polymer waste and treating the wastewater generated in the process. For the quantification of different polymeric waste was carried out a data collection in the Association of Selectors of Recyclable Materials (ASMAR). Where, also were collected the packages of HDPE, LDPE, PP, which were characterized by their degree of contamination and were subsequently used in the washing process. The washing process was carried out in three phases (pre-wash, washing and rinse), and using different cleaning products. Regarding the treatment of the effluent was adopted a physical-chemical process via the coagulation / flocculation, sedimentation, followed by filtration. The following coagulants were used: chitosan powder, chitosan diluted in acetic acid, tannin SG, tannin SL and aluminum sulfate. The results from the quantitation of different polymeric residues collected by ASRM demonstrated that the most representative resins in 2014 were the LDPE, with 33.87% and 21.74% with HDPE. Regarding the characterization of polymeric waste depending on their level of contaminants was possible to verify that packages of PP and HDPE, even though they come from selective collection still contained a high level of contaminants, unlike LDPE packaging. As the washing process, it was possible to ascertain that the three stages developed, consisting of an efficient sequence for obtaining clean polymeric residues and suitable for recycling. Furthermore, the combination of sulfonic acid with lauryl and sodium hydroxide showed be more efficient to the other conditions tested in the washing step. Regarding the treatment of the wastewater, the results indicated that the use of aluminum sulphate coagulating was the most efficient in the removal of turbidity. Also was noted the importance of completing the process of coagulation / flocculation before the filtration. From the results obtained in the characterization process of the raw and treated wastewater it was possible to verify that the chosen treatment is effective and appropriate, once the values removed for most of the analyzed parameters were higher than 90%, including turbidity, suspended solids, fixed and volatile amounted to nearly 100% removal. Therefore, the washing process applied was efficient for obtaining clean polymeric materials and favorable to recycling and the method employed for treatment of wastewater also played a great role, since it allows the obtention of a treated wastewater with appropriate quality standards, which gives safety and reliability for its reuse in the washing process of polymeric residues.